Chemical nucleases are a robust alternative for RNase H cleavage of human ribosomal RNA. - Hagen Wesseling; Dennis Krug; Marvin Wehrheim; Michael W Göbel; Stefanie Kaiser (PLoS ONE)
Besides the abundant ribosomal and transfer RNA transcripts (rRNA and tRNA, respectively), there are tens of thousands of long coding (mRNA) and non-coding transcripts (lncRNA) within each cell whose modification profiles have not yet been elucidated. One reason for this is that most mRNAs and lncRNAs are low abundant and their purification prior to direct modification analysis by mass spectrometry (LC-MS) is highly challenging. State-of-the-art mRNA purification protocols are based on poly(A) enrichment with subsequent rRNA depletion using either magnetic pulldown assays or RNase H. While these methods are well suited for RNA sequencing, where residual rRNA content can be acceptable, LC-MS analysis of mRNA requires samples with less than 1% rRNA and higher yields, making the existing methods close to unaffordable. Thus, a new principle for low-cost (pre)mRNAs and lncRNAs preparation from total RNA will be beneficial for LC-MS analysis but also sequencing approaches. Here, we show that the use of ARRR (artificial ribosomal RNA remover: conjugates of standard DNA probes and a small-molecule chemical nuclease) is suitable for rRNA cleavage. In addition, ARRR has a higher target specificity compared to E. coli RNase H using regular DNA probes and only limited off-target RNA degradation is observed with ARRR. In summary, we present a promising tool with high potential to remove overly abundant rRNA, which might be used for enrichment of lncRNAs and (pre)mRNAs for downstream sequencing and MS-based analysis.